Peran Zakat, Infak, Sedekah Dalam Mewujudkan Sustainanble Development Goals Di Indonesia - Rizky Putra Utama (Kutubkhanah, 2021)
This research is a study to see the role of zakat, infaq, and alms in realizing sustainable development goals in Indonesia. The SDGs are a goal that is mutually agreed upon by the member states of the United Nations (UN) with the aim of creating prosperity and a decent life for every citizen. This is of course in line with the target of zakat in Islam, as an instrument for distributing wealth from people who have excess assets to people who lack assets. So the purpose of this study is to see how big the role of zakat, infaq, and alms in supporting the achievement of the SDGs goals in Indonesia. From the results of the analysis that has been carried out, it was found that zakat, infaq, and alms have a positive role in achieving the SDGs goals in Indonesia with five (5) program pillars: economy, health, education, da'wah, social humanity. Zakat, infaq, alms play an important role in the funding sector for eight (eight) targets of zakat recipients: (1) poor, (2) poor, (3) amil, (4) converts, (5) slaves, (6) Gharimin, (7) fii sabilillah, (8) ibn sabil. With the biggest role towards the SDGs goals: eradicating poverty, eradicating hunger, decent health, and quality education.